ASSETS OF MODEL METRO STATION AND THEIR CRITICALITY - Tomáš Kertis; Dana Procházková (Acta Polytechnica CTU Proceedings)
The paper deals with the identification of protected assets in the model metro station, which is a part of critical infrastructure in Praha; and with the identification of their criticality. A metro station is used by a lot of people and it involves many expensive components and devices with interdependences which form a system of systems. The system, its components and fittings are very vulnerable to damages from disasters of many kinds. The first step of ensuring metro station safety is the identification of basic metro assets which are important for safe metro operation and for human (employee and passengers) security and environment safety; and the other is determination of criticalities of considered assets with taking into account all relevant sources of hazards. These facts are input data for further processes which are important for safe metro operation under the different conditions.